In forging the possibilities: the "Krupp" Campo Limpo Paulista in the paths of workers (second half of the 20th century and early 21th century) (Tempo e Argumento, 2013)
This article presents ponderations on trajectory of workers who have experienced the workspace in ThyssenKrupp-Campo Limpo Paulista, from the half of the 20th century. The interest was to discuss the range of possibilities some workers, analyzing contradictions and differentiations in the memories they produce on labor relations, associated with the class condition who they share, involving relations between country and city, as well as the process of industrial expansion. In doing so, the proposal calls into question the supposed homogenizing experience of "being metallurgical" and the analytical construction based on structural alterations in the work world dinamics. The reflections produced they attempt to highlight the inequalities and pressures that emphasize the practices of workers in capitalist society and, at the same time, they highlight the exploration who live and how they interpret the relations and paths who decide cope.
Keywords: workers; trajectories; labor relations; ThyssenKrupp